Early outcome of incisional hernia repair using polypropylene mesh: A preliminary report - Udo, Isaac A. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: The use of prosthetics for open repair of incisional hernia is very recent in our practice. We highlight our experience repairing incisional hernias with polypropylene mesh. PATIENTS AND METHODS: Patients presenting with incisional hernia >5 cm in length or width received open polypropylene mesh repair and were followed for two years. Data obtained included age, sex, primary surgery causing the hernia, the length of the fascial defect and previous attempts at repair. Post-operative wound complications were recorded. The integrity of the scar and patient satisfaction or concerns with the repair was assessed at each visit. RESULTS: Nineteen females with a mean age of 35 years (range 30-54) underwent repair; most arising from obstetric or gynaecological procedures. Sixteen (82.2%) had midline, 2 (10.5) transverse and 1 (5.3) Pfannenstiel scars. One patient had no previous repair (R0), 7 had undergone one repair (R1), 9 had undergone two repairs (R2) and 1 had three previous repairs (R3). The length of fascial defects ranged from 8 to 18 cm and seroma collection and stitch sinus were the common problems encountered. Two (10.5%) recurrences were recorded in two years. CONCLUSION: Open mesh repair of incisional hernia carries a low risk of infection and recurrence in two years.